2014
DOI: 10.3748/wjg.v20.i42.15727
|View full text |Cite
|
Sign up to set email alerts
|

GW4064, a farnesoid X receptor agonist, upregulates adipokine expression in preadipocytes and HepG2 cells

Abstract: The FXR agonist through regulating, at least partially, the expression of adipokines and their receptors could offer an innovative way for counteracting the progress of metabolic diseases such as nonalcoholic fatty liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…This receptor is well known for its capacity to mediate insulin signaling via augmenting the release of adiponectin and the translocation of GLUT4 to the surface of skeletal myocytes and adipocytes [47,48]. Other studies have documented the cross-talk between FXR and PPARγ in alleviating liver fibrosis [49] and other metabolic diseases like nonalcoholic fatty liver disease [50]. Hence, these data may correlate to the present work and emphasize the possible involvement of these two receptors in mediating CDCA-related neuroprotection and insulin sensitivity, seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This receptor is well known for its capacity to mediate insulin signaling via augmenting the release of adiponectin and the translocation of GLUT4 to the surface of skeletal myocytes and adipocytes [47,48]. Other studies have documented the cross-talk between FXR and PPARγ in alleviating liver fibrosis [49] and other metabolic diseases like nonalcoholic fatty liver disease [50]. Hence, these data may correlate to the present work and emphasize the possible involvement of these two receptors in mediating CDCA-related neuroprotection and insulin sensitivity, seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…3 , IR9 is identified as a novel FXRE that is involved in up-regulation of SOCS3 in HCC cells, which means SOCS3 is a new direct target gene of FXR. Besides, previous studies have demonstrated that another nuclear receptor PPAR γ could promote SOCS3 expression [ 8 , 31 ], and FXR could up-regulate PPAR γ [ 32 , 33 ]. So FXR may also indirectly enhance the expression of SOCS3 via inducing PPAR γ.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin‐deficient ob/ob mice display markedly reduced levels of energy expenditure and become an important model for MetS study (Flier, 2004). Several FXR agonists have been reported to enhance the expression of leptin in 3T3‐L1 cells and adipose tissue (Shihabudeen, Roy, James, & Thirumurugan, 2015; Xin et al, 2014). In breast malignancy, FXR activation has been reported to inhibit leptin signalling (Giordano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%